2008
DOI: 10.1111/j.1745-4514.2008.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMIZATION OF THE PRODUCTION OF HYDROLYSATES FROM GRASS CARP (CTENOPHARYNGODON IDELLA) SKIN USING ALCALASE

Abstract: Protein hydrolysate was produced from grass carp skin using Alcalase. Hydrolysis conditions were optimized by using a response surface methodology (RSM). A model equation was proposed with regard to effects of temperature (T), pH, enzyme/substrate (E/S) ratio (%v/w of minced skin) and time (t) on degree of hydrolysis (%DH). The optimum values for T, pH, E/S ratio and t were found to be 59.74C, 8.25, 1.70% and 83.83 min, respectively. Regression coefficients indicated that all linear forms T, pH, t and E/S rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…The range of the degree of hydrolysis for N. japonicus and E. volitans muscle protein was from 29.12 to 42.15% and 21.21 to 43.21%, respectively. In this study the value of degree of (DH) for both fish muscle protein was higher than DH of Grass carp skin, 1.1-15.2% (Wasswa et al 2008) and silver catfish frame, 6.25 to 21.38% (Amiza et al 2011) but lower than degree of hydrolysis of Catla viscera, 34.23-49.65% (Bhaskar et al 2007). The difference in degree of hydrolysis maybe because of the difference in the part of fish used in hydrolysis, difference in fish species and difference in enzyme used (Bhaskar et al 2007).…”
Section: Optimization Of Hydrolysis Conditions By Response Surface Mecontrasting
confidence: 46%
“…The range of the degree of hydrolysis for N. japonicus and E. volitans muscle protein was from 29.12 to 42.15% and 21.21 to 43.21%, respectively. In this study the value of degree of (DH) for both fish muscle protein was higher than DH of Grass carp skin, 1.1-15.2% (Wasswa et al 2008) and silver catfish frame, 6.25 to 21.38% (Amiza et al 2011) but lower than degree of hydrolysis of Catla viscera, 34.23-49.65% (Bhaskar et al 2007). The difference in degree of hydrolysis maybe because of the difference in the part of fish used in hydrolysis, difference in fish species and difference in enzyme used (Bhaskar et al 2007).…”
Section: Optimization Of Hydrolysis Conditions By Response Surface Mecontrasting
confidence: 46%
“…Hydrolysis was effective in improving the EC of hydrolysates. Related findings have indicated that enzymatic hydrolysis of tilapia and grass carp skin (Wasswa et al, 2007) produced hydrolysates with higher emulsifying capacity. …”
Section: Emulsifying Capacitymentioning
confidence: 91%
“…It is proposed that high oil absorption capacity of Roselle seed protein hydrolysates may give an advantage for their consideration in the formulation of food products such as cake, sausages, salad dressings and mayonnaise. Wasswa et al (2007) also produced protein hydrolysates with OHC.…”
Section: Oil Holding Capacitymentioning
confidence: 99%
“…It is important, therefore, to determine the conditions under which to apply enzymatic hydrolysis to produce the best possible response or product (Wasswa et al . ). It is also vital to know which of these factors are critical and the interactions that occur between the factors.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, the efficiency of enzymatic hydrolysis is greatly influenced by factors such as the enzyme concentration, reaction temperature and pH. It is important, therefore, to determine the conditions under which to apply enzymatic hydrolysis to produce the best possible response or product (Wasswa et al 2008). It is also vital to know which of these factors are critical and the interactions that occur between the factors.…”
Section: Introductionmentioning
confidence: 99%